A D-Shaped Photonic Crystal Fiber Refractive Index Sensor Coated with Graphene and Zinc Oxide - Liang, Han (Sensors (Basel), 2020)
A surface plasmon resonance (SPR) sensor based on a D-shaped photonic crystal fiber (PCF) with an uncomplicated structure is proposed to detect the change of refractive index of liquid analytes, and numerical simulation is carried out by the finite element method (FEM). Using silver as the plasmonic metal, the performances of the SPR-PCF sensor coated with a graphene layer and zinc oxide (ZnO) layer were assessed. The sensor designed is only coated with material on the polished surface, which makes the sensor production uncomplicated and solves the problems of filling material in the hole and coating on the hole wall. The effects of structural parameters such as graphene layer thickness, silver layer thickness, ZnO thickness, lattice spacing and manufacturing tolerance of blowhole diameter on the sensor performance were numerically simulated. The numerical results show that the sensitivity of the SPR-PCF sensor coated with 25 nm ZnO is highest in the ZnO thickness range from 10 to 25 nm. In the refractive index range of 1.37–1.41 for liquid analyte, the maximum sensitivity and corresponding resolution reach 6000 nm/RIU and 1.667 × 10(−5), respectively. In addition, the sensor has good stability and high structural tolerance under the tolerance of ±5% of blowhole diameter. This work has wide application value in the detection of biochemical analytes, water pollution monitoring, food quality, and medical diagnosis.